Report of the Central Committee of the Rumanian Communist Party on the activity of the party in the period between the 8th congress and the 9th congress of the Rumanian Communist Party, July 19, 1965 (Agerpres, 1965)
Documents, articles and information on Rumania. 9th congress of the Rumanian Communist Party.